Disparities in Entrepreneurial Orientation and Openness to Innovation Among Budapest, the Pest Region, and Other Regions - Bujáki, János; Vinogradov, Szergej (Studia Mundi – Economica, 2024)
Literature studies focusing on entrepreneurial orientation or openness to innovation mainly focus on large enterprises and multinational companies. Micro, small and medium-sized enterprises (MSMEs) are under-researched in Europe, however, their contribution to employment, balance of trade, and GDP is broadly acknowledged among scholars. Experiences gathered through a qualitative study conducted with owner managers of enterprises of all size categories preceded as well as helped to better establish and design our quantitative survey as recommended in various studies in international literature. This paper aims to examine the disparities in entrepreneurial orientation and openness to innovation between three separate regions in Hungary. Analyses were based on discovering statistically significant differences in terms of the region and the size category of companies. The study applied principal component analyses, Kruskal-Wallis, and Mann-Whitney nonparametric tests.
Keywords: Central Hungary; MSMEs; innovation; entrepreneurial orientation; openness to innovation